Time Structures and the Healing Aesthetic of Joseph Boyden’s Three Day Road - Gordon, Neta (Studies in Canadian Literature, 2008)
Joseph Boyden’s historical novel Three Day Road (2005) portrays the discrimination experienced by Canadian Aboriginal fighters during the Great War. In his acknowledgements, Boyden states his intention to "honour" those soldiers, suggesting the wish to commemorate and/or to redress past injustice. Like many recent Canadian historical novelists, he probes the darker phases of our history to interrogate both past and current social policy and practice. While such fiction often focuses on nationalist narratives, Boyden confronts the way the Aboriginal is written in (or out of) history by constructing a dialectic of time structures — historical, sacred, and genealogical. He thereby renders visible the interactions between historical recovery and mythmaking, but also privileges deconstruction that is constructive: what Laura Groening calls a "healing aesthetic."